The Taliban phenomenon : Afghanistan (1994-1997) / Kamal Matinuddin. - Matinuddin, Kamal (Oxford University Press, 2000)
This work gives an account of the origin, aims and objectives of the Taliban movement. The reasons for their success are examined and the repercussions of an ultra religious regime in Kabul on the security of Pakistan and its neighbours are brought out.